0084 The Evidence Base For Interprofessional Debriefing. (1st November 2014) - Gale, Thomas; O'Connor, Anita; Endacott, Ruth
Abstract : Background/context: Best practice simulation based education involves team based scenarios with members playing their own professional roles in order to improve context and authenticity. 1 Yet the Centre for the Advancement of Interprofessional Education (CAIPE) report in 2012 highlighted the fact that many educators feel under-prepared for their role in interprofessional as compared to uni-professional settings and the skill of the debriefer is known to be the strongest independent predictor of the overall quality of simulation encounters. 2 Methodology: We conducted a systematic review to examine the evidence base for interprofessional debriefing. A total of 217 papers published between January 2003 and December 2013 were identified using the search protocol. Following screening of abstracts, 31 full-text articles were assessed for eligibility and 23 studies were judged acceptable for inclusion in the systematic review. Results: A number of common concepts were included in the different approaches to debriefing, sometimes in differing combinations and with different mixes of professions. Common themes were the need to create a supportive learning environment, provide specific debrief training for faculty and focus on a few but critical performance issues during the debrief. Various frameworks and measures of debriefing quality have been studied using interprofessional simulation but there is a lack of high quality research in this area. Conclusions and recommendations: Validated debriefing frameworks and quality metrics have been identified which warrant further research and application for interprofessional simulation. References: McGaghie WC, Issenberg SB, Petrusa ER, Scalese RJ. A critical review of simulation based medical education research: 2003-2009. Med Educ 2010;44(1):50–63 Fanning RM, Gaba DM. The role of debriefing in simulation based learning. Simulation in Healthcare 2007;2(2):115–25